Ethnopharmacological Field Study of Three Q'eqchi Communities in Guatemala - Vargas, Jorge Mario; Andrade-Cetto, Adolfo (Frontiers in Pharmacology, 2018)
Mesoamerica is well known for the Mayan civilization, which flourished in this region during pre-Columbian times and made use of plant diversity for medicinal purposes. Currently, there are 21 Mayan ethnic groups in Guatemala, including the Q'eqchi'. The use of medicinal plants is still prevalent among them, they have been an important medicinal source for the population. The present study aims to compile traditional knowledge of the use of medicinal plants from three Q'eqchi' communities in Alta Verapaz, Guatemala and identify the important medicinal plants that are currently being used to treat relevant diseases. The study also aims to determine the relative importance of the identified species to propose new species for further pharmacological studies. Based on the cultural richness and the low level of perturbation of the vegetation, we selected the Q'eqchi' communities of Sanimtaqá, Santo Domingo de las Cuevas and Chirrepec in Alta Verapaz, Guatemala. There, semi-structured interviews were conducted between June 2013 and December 2014 with common people. Plant-related questions and certain sociocultural contexts of the informants were included. Herbarium specimens for identification were collected with the help of the informants in their gardens with people from each community. The data were interpreted using a non-qualitative analysis method. The results of direct interviews were analyzed using quantitative tools, including the informant consensus factor, the fidelity level and use reports. A total of 169 interviews were conducted. 137 species of plants with medicinal uses were identified, which were described 2055 times. These species belong to 59 families and 117 genera. Gastrointestinal conditions and pain/fever had the highest number of plant species uses for treatment. The main gastrointestinal conditions included diarrhea (Nume'sa'), stomach pain and worms (Luqum), while the pain/fever classification included headaches (rail jolom) and fevers (Tiq'). The most important cultural condition is called Chaquiq'yaj, the symptoms of the disease; diarrhea, vomiting, fever, lack of appetite, and thirst could be associated with a gastrointestinal. Conclusions: After analyzing the data, we can conclude that; Ageratina ligustrina, Catopheria chiapensis, Baccharis inamoena, Peperomia maculosa, Baccharis salicina, Clinopodium brownei, Calea integrifolia and Smallanthus maculatus var. maculatus are the most culturally relevant species.